Bioethics and nursing: an interface in care - Campos Pavone Zoboli, Elma Lourdes; Natália de Araujo Sartório (O Mundo da Saúde, 2006)
From the beginning of the history of modern nursing, ethical parameters constitute a primordial question for its practice. Throughout the process of the nursing profession configuration, the vocational image has progressively given its place to the professional one, and it made technical qualification important, leading to the inclusion of ethical reflections. Currently bioethics, with its different approaches, combines with nursing’s historical-social construction, bringing to it new perspectives regarding giving an answer to challenges stemming from the conjoining of ethics and technique. Principialism contributes for the understanding of the importance of encouraging and protecting the autonomy of the professional and the patient in cares practice, respecting the limits of beneficence, non-maleficence and justice. The emphasis on care, by its turn, aims to promote the confidence and the mutual responsibility people among themselves. The present article has as its aim to present bioethics as a bridge that can lead to the interconnection of care-technique with care-ethics, of “treating” with “taking care of”, integrating principles and technical competence, in an atmosphere of care and responsibilization for the suffering and health of the other.